Studi Sistematik Mengenai Misi dan Teologi Misi Alkitabiah dan Holistik serta Koherensinya dengan Pelayanan Gereja: Systematic Study of Biblical and Holistic Mission and Mission Theology and Their Coherence with Church Ministry - Marde Christian Stenly Mawikere (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2022)
This article is a systematic-doctrinal study of Biblical and holistic Mission and Mission Theology. This includes a study of the doctrines of the complete nature of God, the whole creation, the whole human being, the complete salvation and the whole ministry as well as the biblical doctrine of the Kingdom of God and its comprehensive scope. The results of this study confirm that there is no substantial separation between the sacred or sacred with the secular or profane, even between personal and social elements. In the Bible, mission includes both spiritual and material elements, and is manifested in the totality of harmony between God, humans and all creation in a holistic manner. Mission consists of ministries of evangelism and humanization, internal conversion and restoration of social situations and conditions, vertical faith and horizontal love. The Bible teaches that the problem of sin is not only the problem of the individual human being that has been corrupted but also the problem of the system or structure that has been corrupted. In the end, it will be recommended a doctrine of a holistic ministry for church that touches all elements of humanity, spiritual, physical, emotional, mental, and social and restores all creation, namely the earth which belongs to God in the Lord Jesus Christ, the redeemer and the great restorer. Keywords: Mission, Theology, Biblical, Holistic, Doctrine.